ADJUVANT EFFECT OF TUBULAR IMMUNOSTIMULATING COMPLEXES MODIFIED BY ECHINOCHROME A, TOWARDS A PORE PROTEIN FROM YERSINIA PSEUDOTUBERCULOSIS - A. V. Tsybulsky (SPb RAACI, 2014)
Abstract. We investigated immunogenic properties of vaccine constructs based on lipid-saponin tubular immunostimulating  complexes  (TI-complexes),  and  an  individual  antigen,  i.e.,  monomeric  and  trimeric forms of porin isolated from Yersinia pseudotuberculosis. An opportunity of enhanced immune response to TI-embedded porin was shown upon addition of echinochrome A (ECA) from sea urchin Scaphechinus mirabilis to TI-complexes. Immunization of mice with such a vaccine preparation results into a more intense specific humoral immune response to monomeric and trimeric forms of porin. (Med. Immunol., 2011, vol. 13, N 2-3, pp 139-144)